Guidance on Implementing an Oral Chemotherapy Drug Repository Program in a Medically Integrated Pharmacy Setting. Issue 7 (July 2021) - Monestime, Shanada; Magallon, Tara; Jenkins, Lauren; Page, Ray
Abstract : Oncology drug repository programs allow patients to donate oral chemotherapy that can be redispensed to patients in need and could ultimately reduce drug waste. Medically integrated pharmacies can serve as a platform for drug repository programs because of the integration of healthcare providers and pharmacists at one location, facilitating an effective transition from donation to redispensing. Before implementing a program, pharmacies should consider state laws regarding who can donate medications, the type of setting (including open or closed systems), as well as how to assess the quality of the medication donated, expiration dates, storing and maintenance of a separate inventory, written policies and procedures, and a priority list for dispensing medications to patients. In this article, we provide the initial steps to assist states and oncology pharmacists interested in developing a drug repository program.